2018
DOI: 10.1016/j.heliyon.2018.e00711
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment modifies the association of wealth status with elevated blood pressure in the Ghanaian population

Abstract: The relationship between wealth and blood pressure (BP) in developing countries is unclear and it is important to understand how the socioeconomic environment influences BP in an African setting. Our objective was to determine the wealth differences in BP in the Ghanaian population and to clarify whether the relationship is modified by education level. Data from the 2014 Ghana Demographic and Health Survey was analyzed. A total of 9396 women and 4388 men were sampled nationwide and interviewed for the survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…The positive association between educational level and hypertension among females is in contrast to findings from high-income countries, where studies have found a higher level of education to be protective against hypertension [44,45]. Our finding, however, is supported by studies from Ghana and other low-income and middle-income countries, where higher socioeconomic status is associated with higher BP and hypertension prevalence [46,47]. In these settings, socioeconomic development is associated with the adoption of unhealthy lifestyles, such as less physical activity and a more sedentary lifestyle, resulting in more obesity and hypertension [48].…”
Section: Discussion Of Key Findingscontrasting
confidence: 87%
“…The positive association between educational level and hypertension among females is in contrast to findings from high-income countries, where studies have found a higher level of education to be protective against hypertension [44,45]. Our finding, however, is supported by studies from Ghana and other low-income and middle-income countries, where higher socioeconomic status is associated with higher BP and hypertension prevalence [46,47]. In these settings, socioeconomic development is associated with the adoption of unhealthy lifestyles, such as less physical activity and a more sedentary lifestyle, resulting in more obesity and hypertension [48].…”
Section: Discussion Of Key Findingscontrasting
confidence: 87%
“…The main strength of this study lies in the use of nationally representative data. The sampling strategy–multi-stage—employed by the DHS usually helps to minimize selection bias [ 39 ]. Also, the DHS employs standard data collection instruments and procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between socioeconomic status and hypertension has been well established 15 as either a cardiovascular risk factor or a means to predict lifestyle 35,36 . The socioeconomic statushypertension gradient appears to differ by development region with a positive gradient often seen in LMICs 17,29 and a negative in HICs 15 . The results of this study are contrary to those identified in LMICs, but this inverse association may indicate that the country reached an advanced development stage 19 , as it has been observed in China with exception of some rural areas 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The educational level is reported as the best marker 35 and it can modify the effect of other socioeconomic determinants 29 once well educated people are more likely to be employed, have a better work and economic conditions, social and psychological resources, and to adhere a healthier lifestyle 38 . A low level of schooling is associated with the perception of stress and with high BMI and waist circumference, what contribute to the increase of blood pressure 16 .…”
Section: Discussionmentioning
confidence: 99%